The impact of human-facilitated selection on the gut microbiota of domesticated mammals. Issue 9 (25th July 2019) - Alessandri, Giulia; Milani, Christian; Mancabelli, Leonardo; Mangifesta, Marta; Lugli, Gabriele Andrea; Viappiani, Alice; Duranti, Sabrina; Turroni, Francesca; Ossiprandi, Maria Cristina; van Sinderen, Douwe; Ventura, Marco
ABSTRACT: Domestication is the process by which anthropogenic forces shape lifestyle and behavior of wild species to accommodate human needs. The impact of domestication on animal physiology and behavior has been extensively studied, whereas its effect on the gut microbiota is still largely unexplored. For this reason, 16S rRNA gene-based and internal transcribed spacer-mediated bifidobacterial profiling, together with shotgun metagenomics, was employed to investigate the taxonomic composition and metabolic repertoire of 146 mammalian fecal samples, corresponding to 12 domesticated–feral dyads. Our results revealed that changes induced by domestication have extensively shaped the taxonomic composition of the mammalian gut microbiota. In this context, the selection of microbial taxa linked to a more efficient feed conversion into body mass and putative horizontal transmission of certain bacterial genera from humans were observed in the fecal microbiota of domesticated animals when compared to their feral relatives and to humans. In addition, profiling of the metabolic arsenal through metagenomics highlighted extensive functional adaptation of the fecal microbial community of domesticated mammals to changes induced by domestication. Remarkably, domesticated animals showed, when compared to their feral relatives, increased abundance of specific glycosyl hydrolases, possibly due to the higher intake of complex plant carbohydrates typical of commercial animal feeds. Abstract : Domesticated–feral animal gut microbiota comparisons.